Eliminating the invading extracellular and intracellular FnBp+ bacteria from respiratory epithelial cells by autophagy mediated through FnBp-Fn-Integrin α5β1 axis - Meng, Meiqi; Wang, Jiachao; Li, Hongru; Wang, Jiao; Wang, Xuan; Li, Miao; Gao, Xue; Li, Wenjian; Ma, Cuiqing; Wei, Lin (Frontiers in Cellular and Infection Microbiology, 2024)
Background We previously found that the respiratory epithelial cells could eliminate the invaded group A streptococcus (GAS) through autophagy induced by binding a fibronectin (Fn) binding protein (FnBp) expressed on the surface of GAS to plasma protein Fn and its receptor integrin α5β1 of epithelial cells. Is autophagy initiated by FnBp+ bacteria via FnBp-Fn-Integrin α5β1 axis a common event in respiratory epithelial cells? Methods We chose Staphylococcus aureus (S. aureus/S. a) and Listeria monocytogenes (L. monocytogenes/L. m) as representatives of extracellular and intracellular FnBp+ bacteria, respectively. The FnBp of them was purified and the protein function was confirmed by western blot, viable bacteria count, confocal and pull-down. The key molecule downstream of the action axis was detected by IP, mass spectrometry and bio-informatics analysis. Results We found that different FnBp from both S. aureus and L. monocytogenes could initiate autophagy through FnBp-Fn-integrin α5β1 axis and this could be considered a universal event, by which host tries to remove invading bacteria from epithelial cells. Importantly, we firstly reported that S100A8, as a key molecule downstream of integrin β1 chain, is highly expressed upon activation of integrin α5β1, which in turn up-regulates autophagy. Conclusions Various FnBp from FnBp+ bacteria have the ability to initiate autophagy via FnBp-Fn-Integrin α5β1 axis to promote the removal of invading bacteria from epithelial cells in the presence of fewer invaders. S100A8 is a key molecule downstream of Integrin α5β1 in this autophagy pathway.